Diet composition of Asiatic lions in protected areas and multi-use land matrix - Ram, Mohan; Sahu, Aradhana; Srivastava, Nityanand; Chaudhary, Rohit; Jhala, Lahar (Journal of Vertebrate Biology, 2023)
Comparative studies on the diet of large felids in protected areas (PAs) and surrounding multi-use landscapes are important for their conservation. The Asiatic lion is an endangered felid distributed in Gir PA and the surrounding multi-use land matrix. Based on scat analyses, we assessed the dietary composition of Asiatic lions. The frequency of occurrence (FOO), biomass consumption model, dietary niche breadth and dietary overlap index was used to quantify diet. The Asiatic lion ate more wild prey (74%) than domestic livestock (26%) in the Gir PA. In contrast, lion diets comprised 51% wild prey and 42% domestic livestock in the multi-use land matrix. Sambar contributed most (38%) to the diet in PAs, while blue bull most (29%) in the multi-use land matrix. However, diet diversity and niche breadth were similar between these two areas. The dietary overlap in the lions' diet between these two areas was 0.52. The results suggest that large-size wild ungulates are the main prey species in Gir PA, while in the surrounding multi-use land matrix, both large wild ungulates and domestic livestock are the main prey. The present study may help future lion conservation management decisions.